Penyuluhan Osteoarthritis Lutut pada Komunitas Senam Sehat RW 6 Pabelan Kecamatan Kartasura Kabupaten Sukoharjo - Yulia Nafizah Mawarni; Khansa Syafira; Raden Andrea Zalfa Zaki; Wahyu Tri Sudaryanto (Jurnal Pengabdian Masyarakat, 2022)
Osteoarthritis is a disease that is often found in the elderly. The prevalence of knee osteoarthritis shows that adults in the 60-64 year age group are 22%, while men with the same age group are found to have 23% of right knee osteoarthritis while the left knee is 16.3%. While osteoarthritis in women, the right knee is 24% and the left knee is 24.7%. The incidence of knee osteoarthritis in Indonesia is around 30%, namely at the age of 40-60 years, and 60% at the age of more than 61 years. The partner of this service activity is the Healthy Gymnastics Community RW 6 Pabelan, Kartasura District, Sukoharjo Regency in preventing osteoarthritis and knowing the understanding of the education. The educational method provided by the lecture method is delivered with poster media. To measure the level of understanding and knowledge, pre-test and post-test were carried out on 8 respondents with the pre-test results obtained that 1 person (12.5%) had knowledge in the good category, 7 people (87.5%) had sufficient knowledge. and the post-test results obtained 2 people (25%) have knowledge in the sufficient category, 6 people (75%) have knowledge in the good category. Participants were enthusiastic in participating in this activity and there was an increase in understanding by the Healthy Gymnastics Community RW 6 Pabelan, Kartasura District, Sukoharjo Regency about prevention management in osteoarthritis.